raumatic brain injury : caregivers' problems and needs. - Syed Hassan, Syed Tajuddin; Khaw, Wan Fei; Abdul Raman, Rosna; Jamaludin, Husna (Nepal Medical Association, 2011)
Traumatic brain injury (TBI) is an increasingly major world health problem. This short review using the most pertinent articles on TBI caregiving problems and needs highlights the pressing issues. Articles focusing on both TBI-caregivers' problems and needs are rarely found, especially for developing countries. Most TBI-caregiving is done by family members, whose altered lives portend burden and stresses which add to the overwhelming demand of caring for the TBI-survivor. Lack of information, financial inadequacy, anxiety, distress, coping deficits, poor adaptability, inadequate knowledge and skills, and a poor support system comprise the major problems. Dysfunctional communication between caregivers and care-receivers has been little researched. The major needs are focused on health and rehabilitation information, financial advice and assistance, emotional and social support, and positive psychological encouragement. In time, health information needs may be met, but not emotional support. Information on TBI caregiving problems and unmet needs is critical to all relevant healthcare stakeholders.